2020
DOI: 10.1007/s00345-020-03388-5
|View full text |Cite
|
Sign up to set email alerts
|

New computed tomographic predictors of complicated perioperative course of 17.5F mini-percutaneous nephrolithotomy (mini-PNL)

Abstract: Purpose Radiological parameters predicting a postoperative stone-free status (SFS) or a complicated perioperative course of mini-PNL, are scarce. Our aim was to identify such factors for prone 17.5F mini-PNL. Methods A monocentric cohort of 103 cases was retrospectively analysed for factors predicting SFS and relevant complications, i.e. Clavien-Dindo (CD) ≥ 2. Parameters measured on preoperative supine CT included maximal stone diameter, skin-to-stone distance (SSD), ideal tract length (ITL), access angle, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Factors such as prolonged operative time and increased intra-renal pressure intraoperatively may contribute to this. A recent study by Ozimek et al reassuringly demonstrated that IPA was not associated with either SFR or post-operative complications following mini-PNL [ 39 ].…”
Section: Pnlmentioning
confidence: 99%
“…Factors such as prolonged operative time and increased intra-renal pressure intraoperatively may contribute to this. A recent study by Ozimek et al reassuringly demonstrated that IPA was not associated with either SFR or post-operative complications following mini-PNL [ 39 ].…”
Section: Pnlmentioning
confidence: 99%